Indonesia - Russia Bilateral Relations: Efforts To Enhance Digital Economy And Tourism Investment Cooperation - Hendra Manurung; Henky H. P Manurung; Arry Bainus; Rusadi Kantaprawira; Teuku Rezasyah (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Indonesia and Russia's bilateral relations still need to be improved and strengthened in all sectors. Both countries agreed in Jakarta in 2021 to enhance and strengthen bilateral cooperation in politics, law, and security. The commitment to further cooperation made by the two major countries in the Asia Pacific aimed at creating peace and maintaining regional and global security stability. This study aims to elaborate how Indonesia's bilateral relations with Russia enhanced are related to the efforts of both generating digital economic cooperation and attracting foreign investment in Indonesia's leading tourist destinations. This study utilizes the concept of dynamic bilateral relations and the implementation of foreign economic policies. The researchers use qualitative research methods with explanatory writing techniques analyzing the data and information obtained. The liberal approach to mutually beneficial international cooperation is further elaborated and analyzed, particularly in understanding how each country's strategic decisions have an impact on sustaining regional economic growth. The digital economy cooperation built by the two countries still needs to be strengthened to attract more incoming Russian investors in the tourism industry. This research reveals that international cooperation has been carried out by the Indonesian government and stakeholders related to tourism management destinations is done through bilateral cooperation, regional cooperation, and multilateral cooperation. It still needs clear strategies that should be implemented tactically as a strategic effort by the Indonesian government and related stakeholders to sharpen the construction of the national digital economy in the sustainable, inclusive, and quality tourism sector in driving and supporting national economic growth.